Genome-wide identification and functional prediction of circular RNAs in response to heat stress in Chinese Holstein cows. Issue 6 (18th November 2022) - Qi, Ying; Zhang, Lin; Guo, Yuemei; Wang, Jing; Chu, Mingxing; Zhang, Yiming; Guo, Junfei; Li, Qiuling
Abstract: Heat stress (HS) leads to substantial economic loss of dairy industry each year. The negative effect of HS in dairy cows is becoming one of the more urgent issue due to accelerating side-effects of global warming. Various genes are involved in HS response but the information about the role of noncoding RNAs, especially circular RNAs (circRNAs) is largely unknown. In our study, we aimed to investigate the different expression profile of circRNAs between HS and Non-heat-stressed condition (NC) of Chinese Holstein cow's mammary gland. CircRNAs were identified using RNA sequencing and bioinformatics analysis. In total, 37405 circRNAs were detected and 95 were differentially expressed (DE), including 15 downregulated and 80 upregulated circRNAs in HS group compared to NC. Eight circRNAs were randomly selected to verify the RNA sequencing result. Further, Sanger sequencing validated the backsplicing site of the eight circRNAs. Moreover, results obtained from the Quantitative real time PCR (qRT-PCR) showed consistent expression trend with that of RNA sequencing. GO annotation and KEGG analysis suggested that these DE circRNAs probably involved in the energy metabolic regulation. Furthermore, we constructed ceRNA network and the result indicated that these DE circRNAs could regulate lactation through IGF1 and PRL signaling pathway.